THE EFFECT OF TRAINING AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE MEDIATED BY COMPETENCY AT THE CENTER MEDAN PALM OIL RESEARCH - Dini Hendriani; Bunga Aditi; Ilham Mubaraq Ritonga (CV. Radja Publika, 2025)
This study aims to analyze the effect of training and work discipline on employee performance with competence as a mediating variable at the Medan Palm Oil Research Center. The research method uses a quantitative approach with Partial Least Square-Structural Equation Modeling (PLS-SEM) analysis techniques. The study population was 235 employees with a sample of 100 respondents determined using the Slovin formula. Data were collected through a questionnaire with a Likert scale and analyzed using SmartPLS version 3. The results showed that training had a significant positive effect on employee performance (β = 0.419; p = 0.001) and competence (β = 0.354; p = 0.000). Work discipline had a significant positive effect on employee performance (β = 0.551; p = 0.000) and competence (β = 0.147; p = 0.001). Competence had a significant positive effect on employee performance (β = 0.005; p = 0.000). Mediation testing demonstrated that competence mediated the effect of training on employee performance (p=0.002) and work discipline on employee performance (p=0.002). This study emphasizes the importance of developing continuous training and strengthening a culture of discipline to improve employee competence and performance.